IMPLEMENTASI FATWA DSN-MUI NO. 108/DSN-MUI/X/2016 TENTANG PEDOMAN PENYELENGGARAAN PARIWISATA BERDASARKAN PRINSIP SYARIAH PADA DESTINASI WISATA TALAO PAUH KOTA PARIAMAN - Fina Marliza Putri; Dewi Manda Angraini (Jurnal Ekonomi dan Bisnis, 2025)
This re$se$arch was carrie$d out at the$ Talao Pauh Tourism De$stination which is one$ of the$ tourist de$stinations in Pariaman City which strive$s to be$come$ a le$ading tourist de$stination at the$ national and inte$rnational le$ve$l as state$d in the$ vision of Pariaman City, name$ly Pariaman City of Tourism, Trade$, Re$ligious and Cultural Se$rvice$s. . The$ aim of this re$se$arch is to de$te$rmine$ the$ imple$me$ntation of DSN-MUI fatwa no. 108/DSN-MUI/X/2016 at the$ Talao Pauh Tourist De$stination, Pariaman City. The$ me$thod use$d in this re$se$arch is a qualitative$ me$thod with a qualitative$ de$scriptive$ approach. Data colle$ction was carrie$d out by obse$rvation, inte$rvie$ws and docume$ntation. Base$d on this re$se$arch, it can be$ conclude$d that the$ Talao Pauh Tourist De$stination has partially imple$me$nte$d sharia principle$s, including the$ e$xiste$nce$ of place$s of worship, name$ly praye$r rooms, ablution place$s that are$ se$parate$d for me$n and wome$n, the$ e$xiste$nce$ of a choice$ of tourist attractions that do not le$ad to pornography and idolatry such as playgrounds. family, wate$r ride$s, tracking tourist bridge$s, the$ food provide$d at this tourist de$stination is also local culinary de$lights that are$ de$finite$ly halal. Howe$ve$r, the$re$ are$ still aspe$cts that ne$e$d to be$ conside$re$d, name$ly the$ lack of supe$rvision of visiting tourists, such as be$ing a me$ans for couple$s who are$ not ye$t le$gal husband and wife$ and are$ not in accordance$ with the$ DSN-MUI Fatwa be$cause$ tourist de$stinations must be$ prote$cte$d from immorality and adulte$ry. The$n, mainte$nance$ of public toile$t facilitie$s and improving cle$anline$ss around tourist are$as ne$e$d to be$ conside$re$d to e$nsure$ compliance$ with the$ DSN-MUI fatwa that tourist de$stinations must maintain cle$anline$ss, natural sustainability, sanitation and the$ e$nvironme$nt.